I-Narration: Revealing Narrator’s Selfhood - Tonyan, Marika (Armenian Folia Anglistika, 2012)
The present article is aimed to discuss the narrator’s selfhood in I-narrations. The investigation shows that first and third person narrations reveal the identity of the narrator in different ways. If in the first case the narrator introduces himself/herself as an individual, the second version keeps his personality in secret. This difference rests upon the semantic peculiarities of personal pronouns. The altering technique of the two narrations in the same text creates a complex psychological image of the character.